14-2(3p+p)=6(4+p)

Simple and best practice solution for 14-2(3p+p)=6(4+p) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 14-2(3p+p)=6(4+p) equation:


Simplifying
14 + -2(3p + p) = 6(4 + p)

Combine like terms: 3p + p = 4p
14 + -2(4p) = 6(4 + p)

Remove parenthesis around (4p)
14 + -2 * 4p = 6(4 + p)

Multiply -2 * 4
14 + -8p = 6(4 + p)
14 + -8p = (4 * 6 + p * 6)
14 + -8p = (24 + 6p)

Solving
14 + -8p = 24 + 6p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-6p' to each side of the equation.
14 + -8p + -6p = 24 + 6p + -6p

Combine like terms: -8p + -6p = -14p
14 + -14p = 24 + 6p + -6p

Combine like terms: 6p + -6p = 0
14 + -14p = 24 + 0
14 + -14p = 24

Add '-14' to each side of the equation.
14 + -14 + -14p = 24 + -14

Combine like terms: 14 + -14 = 0
0 + -14p = 24 + -14
-14p = 24 + -14

Combine like terms: 24 + -14 = 10
-14p = 10

Divide each side by '-14'.
p = -0.7142857143

Simplifying
p = -0.7142857143

See similar equations:

| 5(2x+8)=7x+20 | | 0.05x+0.04y=420 | | -7-2x=-19 | | -1(3z+4)=6z+-3(3z+2) | | 3(2x+4)-x=11 | | f(x)=3x^2+6x-7 | | 5c-4(9-c)= | | 5c+4c= | | 3(2x+5)-x=11 | | 5c+4n= | | [x-3]=12 | | z+30=16 | | 14+3n=8n-3(1n-4) | | 17=2x+3 | | 4(2x+1)=x+4 | | 18-10(x-1)=4x | | 2-4/2 | | 1/3(5y-1) | | 8+f(4/5)=0 | | -8x-(3x+6)=4-1x | | 5x-4=1-x | | (y^2-4y+3)/(5y^2-40y+35) | | 4y-3(2y-7)=5y+12 | | v^2-v=30 | | x-5+3x/4=-5+7x/4 | | x+2-8=14 | | 28+a+(-48.08)*(1.414213562)=0 | | 2t+3=-12 | | 34+a+(-48.08)*(1.414213562)=0 | | 5(-3b+2)=40 | | 34+a+(-48.08)*1.414213562=0 | | 10+9(x-2)=13x-4(x+4) |

Equations solver categories